Evaluation of setting time and compressive strength of geopolymer paste containing blast furnace slag and zeolite - Maryam Mohammadi Fatideh (Iranian Society of Structrual Engineering (ISSE), 2021)
Production of Portland Cement (PC) is a highly energy-intensive process and causes significant environmental damages. Thus scientists are always after ways to reduce these negative effects and find a more efficient process of producing cement. Geopolymers are amongst materials that are used as a substitute for cement in concrete. Geopolymer consists of one or more source materials containing alumino-silicate with an alkali activator.This study is done for the purpose of evaluating the setting time and compressive strength of geopolymer paste containing blast furnace slag and zeolite. Hence the setting time of geopolymer paste based on blast furnace slag and zeolite activated with sodium hydroxide solution of concentrations 6, 8, 10 and 12 molar and sodium silicate modulus of 2 was measured. In the next step, compressive strength of geopolymer paste samples under curing were gauged in the lab ambient temperature and also in the 60°C temperature.Results showed that with an increase in sodium hydroxide concentration, the setting time increased. Also compressive strength of geopolymer paste containing slag and zeolite rose with the raise of sodium hydroxide concentration. Geopolymer paste samples based on slag, showed increase in compressive strength in sodium hydroxide concentrations 6, 8 and 10 molar. Though with an increase in concentration of sodium hydroxide to 12 molar, compressive strength decreased. Also with an increase in the percentage of zeolite substitute in the source material, setting time increased but compressive strength decreased. Samples cured in 60°C temperature showed better strength, too.